Albania MSME Finance for Growth Assessment - World Bank Group (World Bank, Washington, DC, 2018)
Despite being the backbone of the Albanian economy, micro, small and medium sized enterprises(MSMEs) face difficulties in accessing finance which impedes their growth. MSMEs in Albania aresignificant contributors to the economy. In 2016, MSMEs comprised 99.9 percent of active enterprises and 81 percent of the total number of employed people. According to the World Economic Forum Global Competitiveness Report access to finance is the third biggest constraint in Albania for enterprise development and competitiveness after tax rates and corruption. This is in line with a recent EC survey which found that only 17 percent of MSMEs believe that there are no obstacles to obtaining finance, a number significantly lower than in other comparableeconomies. The number of MSMEs having used bank financing is low compared to the EuropeanUnion (EU) average at 29 percent for overdraft/revolving facilities and 14 percent for other bankloans respectively. At the same time, the number of Albanian MSMEs which financed their operationsfrom retained earnings stands at 24 percent, while 15 percent stated using informal third-party finance (family, friends, etc). The MSME sector is generally characterized by high informality (especially in agriculture), limited availability of collateral, low levels of financial capability, and limited uptake of digital transactions.